KONSEP ULAMA DALAM AL-QUR'AN DAN IMPLIKASINYA PADA WACANA KEPENDIDIKAN ISLAM - Kasuwi Saiban (Ta`Limuna: Jurnal Pendidikan Islam, 2012)
Ulama' are Prophet heirs, because of characteristic, personality, duty and ability they owned so that they are respected. And in Muslim society, "ulama' are group of Muslim society taking place of strategic position. Even the history recognized the "ulama' non eyes as bookish buttonhole, but also as actor and motivator of their society. Scholarship quality of all "ulama' has pushed them to be the guide of society in experiencing day to day life. In Indonesia the term "Ulama” used to articulate the certain social community owning circumstantial membership in the field of Islamic religion. Hence the term "ulama' has experienced the stricture of symptom ( reduction). Its implication is must it him moslem scholar comprehended by as educated man, cendikia, intectual (khoiru ummah). Owner of quality of belief in God circumstantial science and its area. After all, ‘ulama’ has a great dedicated a great deal of roles and contribution in educating Muslim people.